Phytochemical Test and Sunscreen Activities Ethanol Extract of Guava Tangkalak Leaves (Belluciapentamera) - Cahya, Oktania; Dwi Fitri Yani; Muhammad Rayhan; Ayu Wandira; Desi Yana Sari; Rini Handayani; Mega Retha Sefriany (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2024)
One of the most important sources of natural light for life is sunlight, and the skin is the outermost and most significant organ in the human body, making it vulnerable to sunlight exposure. This study aims to determine the biochemistry of secondary metabolite compounds in the guava tangkalak leaves of the plant and their activities as an active ingredient of sunscreen using UV-Vis spectrophotometry. The results of this study indicate that the guava tangkalak leaves plant contains secondary metabolite compounds, such as flavonoids, alkaloids, tannins, saponins, and steroids. The SPF values produced at concentrations of 400, 500, 600, 700, 800, and 1000ppm, SPF values of 2.96, 4.60, 7.70, 10.76, 15.13, and 27.41. The maximum concentration of 1000 ppm protects ultra-categories in SPF.